2018
DOI: 10.21037/jtd.2018.08.54
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of cough in non-small cell lung cancer patients after video-assisted thoracoscopic surgery

Abstract: Background: Cough is a common respiratory complication in non-small cell lung cancer (NSCLC) patients after surgery. Previous studies have proposed a number of risk factors for postoperative cough; however, these studies are mainly based on traditional thoracotomies and tend to lack adequate objective assessment methods. The purpose of this study was to identify the risk factors of cough in NSCLC patients after video-assisted thoracoscopic surgery (VATS) using the Leicester Cough Questionnaire in Mandarin Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 47 publications
7
38
1
Order By: Relevance
“…Approximately 25-50% of patients have been reported to experience cough after lung cancer surgery. [3][4][5] Postoperative cough is known to be related to mediastinal lymph node resection, history of chronic obstructive pulmonary disease (COPD), loss of lung volume, and bronchial scarring. [6][7][8] Postoperative cough may last for an extended period after surgery and can reduce patient quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 25-50% of patients have been reported to experience cough after lung cancer surgery. [3][4][5] Postoperative cough is known to be related to mediastinal lymph node resection, history of chronic obstructive pulmonary disease (COPD), loss of lung volume, and bronchial scarring. [6][7][8] Postoperative cough may last for an extended period after surgery and can reduce patient quality of life (QOL).…”
Section: Introductionmentioning
confidence: 99%
“…The LCQ is a reliable method and has been used in many clinical trials as an outcome measure [13,21,25] . Lin et al [22] described that in patients receiving video-assisted thoracoscopic surgery for lung cancer, the mean postoperative total score was 16.35, which was signi cantly lower than the mean follow-up score after 1 month, but the authors did not provide the data of preoperative levels. In our previous study, we found that thyroidectomy was signi cantly associated with a decreased LCQ score compared to baseline scores, but the study did not report when the LCQ scores returned to preoperative levels.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for postoperative cough following surgical procedures have been occasionally analyzed. Lin et al [22] demonstrated that a long duration of anesthesia time, female sex, subcarinal node resection and lower paratracheal node resection were independent risk factors related to cough in non-small-cell lung cancer patients after surgery. Chen et al [23] reported a correlation between pulmonary surgery and postoperative cough, and the probability of postoperative cough was higher in more invasive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for postoperative cough following surgical procedures have been occasionally analyzed. Lin et al [12] demonstrated that a long duration of anesthesia time, female sex, subcarinal node resection and lower paratracheal node resection were independent risk factors for postoperative cough in patients with non-small cell lung cancer. The correlation between lung surgery and postoperative cough was reported by Chen et al [24].…”
Section: Discussionmentioning
confidence: 99%
“…The LCQ is a reliable method and has been used in many clinical trials as an outcome measure [15,23,26]. Lin et al [12] described that in patients receiving video-assisted thoracoscopic surgery for lung cancer, the mean postoperative total score was 16.35, which was signi cantly lower than the mean follow-up score after 1 month, but the authors did not provide the data of preoperative levels. In our previous study, we found that thyroidectomy was signi cantly associated with a decreased LCQ score compared to baseline scores, but the study did not report when the LCQ scores returned to preoperative levels.…”
Section: Discussionmentioning
confidence: 99%